Discrete torsion in singular G2-manifolds and real LG - Roiban, Radu; Römelsberger, Christian; Walcher, Johannes (Advances in theoretical and mathematical physics, 2002)
International Press of Boston - publishers of scholarly mathematical and scientific journals and books